2013
DOI: 10.1007/s00234-013-1218-x
|View full text |Cite
|
Sign up to set email alerts
|

Motor functions in trumpet playing—a real-time MRI analysis

Abstract: The present study shows that it is possible to measure motor function and its implications on oral as well as pharyngeal cavities during sound generation in brass instruments. These changes seem to follow a reproducible pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The scientific literature to date is limited with regard to describing activity within the mouth during brass performance comparable to the present study. One of the first papers utilizing MRI by Schumacher et al [ 29 ] studied trumpet players, and found that there are concomitant increases in posterior oral cavity area with increasing pitch and loudness. It is noteworthy that these increases were not present in the anterior oral cavity of the performers as these remained small throughout the studied note range.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature to date is limited with regard to describing activity within the mouth during brass performance comparable to the present study. One of the first papers utilizing MRI by Schumacher et al [ 29 ] studied trumpet players, and found that there are concomitant increases in posterior oral cavity area with increasing pitch and loudness. It is noteworthy that these increases were not present in the anterior oral cavity of the performers as these remained small throughout the studied note range.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that movements of the tongue occurring in French horn players are seen during the performance of specific exercises that require the performer to play different notes at different loudness levels (7)(8)(9)(10)(11)(12). The extent to which these movements are coordinated in time is presently unknown, however, such information may be useful to brass students and teachers if coincident movement contributes to successful performance.…”
Section: Original Articlementioning
confidence: 99%
“…Real-time magnetic resonance imaging has been utilized as a method for obtaining descriptive and quantitative kinematic information in a wide variety of applications. Among these are cardiac dynamics (1)(2)(3)(4), speech (5), swallowing (6), and oral cavity movements during brass instrument performance (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…With the recent development of cine magnetic resonance imaging (cine MRI) technology, we can now observe the brass players' oropharyngeal area. Previous studies have used similar technology for professional players of the trumpet (1 player, Kaburagi; 4 12 players, Schumacher 5 ) and French horn (more than 20 players, Iltis [6][7][8] ). Furthermore, Iltis examined amateur-level trumpet, French horn, trombone, and tuba players.…”
Section: Textmentioning
confidence: 99%